Oral surgery considerations in patients at high-risk of complications related to drug intake: A systematic review - D. Morgado-Sevillano; J. Rodríguez-Molinero; C. García-Bravo; J.F. Peña-Cardelles; J.A. Ruiz-Roca; I. García-Guerrero; R Gómez-de Diego (Saudi Dental Journal)
Purpose: This study aims to identify and comprehend the management of the most frequent complications in oral surgery that arise from the consumption of multiple drugs. Materials and Methods: A comprehensive review of 23 articles was conducted, focusing on the complications that arise from the consumption of drugs in patients undergoing oral surgery treatment, in addition to the strategies for prevention and treatment. Results: All the reviewed articles offered insightful knowledge into preventing complications through well-defined protocols that encompass both pre- and post-operative measures. These measures include local interventions such as periodontal treatments, dental prophylaxis, and hygiene instructions, as well as systemic approaches like antibiotic prophylaxis and post-surgical antibiotic coverage. Additionally, specific measures like monitoring prothrombin time with the International Normalized Ratio in patients with coagulation disorders, and implementing hemostatic techniques, were also discussed. Conclusion: The most prevalent complications in oral surgery are hemorrhage in anticoagulated patients, infections in immunosuppressed patients, and osteonecrosis in patients who take antiresorptive drugs. Edema, pain, and inflammation are also common post-operative concerns. When managing high-risk patients pharmacologically, it is crucial to provide effective antibiotic coverage both pre- and post-procedure and to utilize minimally invasive dental procedures with local hemostatic measures.